Profile of chemical dependents under treatment in a therapeutic community in the municipality of Pinheiro – MA (Research, Society and Development, 2022)
Dependence on psychoactive substances is a chronic disease that changes physical, mental, emotional and social aspects. The aim of this study was to assess the profile of institutionalized in a Therapeutic Community through a quantitative, descriptive and cross-sectional survey (n=26) through a questionnaire of sociodemographic data, personal and family history and the International Classification of Diseases-10, whose results were analyzed by means and absolute and relative frequencies. The profile analyzed is 65.4% brown, 80.8% Catholic, 80.8% born in the countryside, 46.2% with incomplete primary education, 73.1% single, with 50% children, 73.1% self-employed, 53.9% with family income from one to three minimum wages, 92.3% without INSS benefit. There is a case of family chemical dependency, mostly alcohol (26.7%), in 57.7% of respondents, whose preferred drug is the same, together with marijuana (34.6%), this is the drug of first use (46.1%). There is chemical dependence on multiple psychoactive substances (76.9%) and marijuana is associated with alcohol, crack and cocaine (15%). Curiosity motivated 46.1% of cases. Of the 50% who presented suicidal ideation, 23.1% tried, 83.4% only once and by hanging (57.1%). The fragility of drug addicts translates into sociodemographic scarcity and vulnerability in their background. The results will contribute to the stratization of care according to the profile of the institutionalized.